A PRAGMATIC STUDY OF PROVERBS AND IDIOMS CONTAINING PROFESSIONAL TERMS (Scientific journal of the Fergana State University, 2026)
This article provides a pragmatic analysis of the role and significance of proverbs and idioms containing professional vocabulary in literary texts.